PENGARUH CEO OVERCONFIDENCE, EXECUTIVE CHARACTERISTICS, CAPITAL INTENSITY DAN PROFITABILITY TERHADAP TAX AVOIDANCE - Sunia Desti Claritsa; Chasbiandani, Tryas; Susilawati (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2024)
This study aims to examine the effect of CEO overconfidence, executive characteristics, capital intensity, and profitability on tax avoidance in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022. This study uses overinvestment to measure the level of overconfidence of a company CEO. Executive characteristics is measured by company risk. Capital intensity is measured by a total fixed asset divided by total asset. Profitability is measured by return on assets (ROA). The tax avoidance is measured by the cash effective tax rates (CETR). The analysis model uses panel data regression using Eviews 12. The sample of this study a use 20 food and beverage companies selected by purposive sampling method. The data used is secondary data in the form of financial statements. The results of this study show that CEO overconfidence has a negative effect on tax avoidance, executive characteristics do not affect tax avoidance, capital intensity has a negative effect on tax avoidance, and profitability has a positive effect on tax avoidance. Keywords: CEO overconfidence, executive characteristics, capital intensity, profitability, and tax avoidance.